Kerusakan Ekosistem Pesisir: Reklamasi Wilayah Jawabannya? - Wattimena, Josina Augustina Yvone; Leatemia, Wilshen (Uti Possidetis: Journal of International Law, 2024)
Reclamation of coastal areas is an activity that is widespread in almost all regions of Indonesia. This activity is a solution to answer the problem of limited land area and to meet development needs. In fact, the reclamation carried out, including in the coastal areas of Ambon City, apparently caused damage to the coastal ecosystem and posed a threat to several coastal areas in Ambon City, which of course directly or indirectly had an impact on the people who live in coastal areas. This research aims to analyze and determine aspects of justice for the environment and society resulting from the reclamation of the coastal areas of Ambon City. This research uses an empirical approach. The results of the research show that the problem of reclamation of coastal areas is very unfair to the people of coastal areas and the environment where they live. Laws that are used as a means of reform to improve aspects of human welfare and protect and preserve the environment apparently cannot be used as legal instruments that are "pro-people" and "pro-justice". In fact, when they experience excesses due to reclamation, they must be given compensation and anti-loss as a form of corrective justice as stated by Aristotle and Thomas Hobbes.